Application of Vector Error Correction Model on Macroeconomic Variables toward Changes in the Composite Stock Price Index - Andini Cahyaning Pratiwi; Akhmad Kusuma Wardhana; Sulistya Rusgianto (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
Macroeconomic variables are still interesting to study because some studies still find inconsistent results and dependence on the dynamics of the capital market and international financial markets, especially when there is turmoil in the domestic and international stock markets. This study aims to analyze the causality and cointegration relationship of macroeconomic variables, namely: interest rates (BI Rate), inflation and exchange rates to changes in the composite stock price index (CSPI) using the Vector Error Correction Model (VECM) method with the analysis tool Eviews 10 using secondary time series data based on the period 1990 to 2021. Exogenous variables tested include the BI rate, Inflation and the Logarithm of the Natural Exchange Rate (LnKurs) while the endogenous variables are the Natural Logarithm of the Composite Stock Price Index (LnIHSG). The results showed that the cointegration test results with Johansen's Cointegration Test found that the movement of the LnIHSG, BI Rate, Inflation and Exchange Rates had a relationship of stability/balance and the similarity of movements in the long term. In the causality test with Granger's Causality Test, there is a unidirectional causality relationship between the BI Rate variable and the LnIHSG variable, while there is a two-way causality between the Foreign Exchange variable and the BI Rate variable and vice versa, as well as a two-way causality relationship between the Exchange Rate variable and the Inflation variable, and vice versa.